KECERDASAN EMOSIONAL SEBAGAI PREDIKTOR PRESTASI BELAJAR SISWA SMA: KAJIAN SISTEMATIS TERHADAP DIMENSI PENGATURAN DAN MOTIVASI DIRI - Basir Jarah Anilon; Ahmad T. Zainal Abidin; Syafii, Hisyam; Halim Purnomo; Azhari, Husain (Al Irfan : Jurnal Ilmu Pendidikan dan Penelitian, 2026)
This study aims to examine the influence of emotional intelligence on the academic achievement of public high school students through a systematic literature review approach. Emotional intelligence is defined as an individual's ability to recognize, understand, manage, and express emotions adaptively, which includes five main dimensions: self-awareness, self-regulation, self-motivation, empathy, and social skills. This study uses a systematic literature review method guided by PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). A literature search was conducted through the Google Scholar, Sinta, and DOAJ databases using the keywords "emotional intelligence", "learning achievement", "emotional intelligence", and "academic achievement" with a publication period of 2014–2024. Of the total 87 articles identified, screening based on title and abstract resulted in 43 articles, then selection based on inclusion and exclusion criteria resulted in 18 articles that met the requirements for in-depth analysis. The inclusion criteria included articles discussing the relationship between emotional intelligence and academic achievement, written in Indonesian or English, having gone through a peer-reviewed process, and published in accredited journals. The synthesis results show that emotional intelligence has a positive and significant influence on the academic achievement of public high school students, with contributions ranging from 21% to 34% (R² = 0.21–0.34; p < 0.05). The dimensions of self-regulation and self-motivation were shown to be the most dominant components in influencing student academic achievement. In addition, this relationship was moderated by factors of self-confidence, parental support, and a conducive school climate. The conclusion of this study confirms that the development of emotional intelligence needs to be systematically integrated into educational programs in schools to produce students who excel academically as well as emotionally and socially mature.